Training of Visual Media Based on Natural Materials as a Learning Facility for Independent Learning at Sdn Kupang 4 Sidoarjo: Pelatihan Media Visual Berbasis Bahan Alam Sebagai Fasilitas Pembelajaran Merdeka Belajar di SDN Kupang 4 Sidoarjo - Wati, Tri Linggo; Wakhidah, Kemil; Rohmah, Jamilatur; Firdaus, Firyalita Sarah; Putra, Moh. Faris Yudiana (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this community service activity is to provide training in making visual media based on natural materials for teachers at SDN Kupang 4 Sidoarjo. The problem faced by partners is the lack of mastery of the element of providing facilities in the learning process, namely not providing media at every learning time. While the SDN Kupang 4 Sidoarjo school is rich in natural potential, because it is located in a pond area with materials that are easy to use as learning media that can be used as learning materials in the teaching and learning process. The methods of implementing these community service activities are: conducting a needs analysis by making observations regarding the problems that exist with partners to be immediately assisted in solving problems, then determining the objectives of the training, conducting education, training, and monitoring and evaluation of the application of media in the learning process. obtained after receiving training in visual media based on natural materials, teachers and students produce a learning media by adjusting the existing theme, then the teacher applies the media in learning activities. So that learning is no longer monotonous but looks fun and meaningful because students become interactive learning through the media that is applied.